The idea of India - Khilnani, Sunil (Penguin Books, 1999)
"Our appreciation of the importance of India can only increase in light of current events in Asia and after the revelations about India's nuclear capabilities. This study addresses the paradoxes and ironies of this the world's largest democracy. Do the old ideas, or idea, of India still hold true - especially now that the country is in the hands of a very different kind of leadership? Can the original idea of India survive its own successes?".